Callous-Unemotional Traits Moderate the Relationship Between Irritability and Threatening Responding - Zhang, Ru; Bashford-Largo, Johannah; Lukoff, Jennie; Elowsky, Jaimie; Carollo, Erin; Schwartz, Amanda; Dobbertin, Matthew; Bajaj, Sahil; Blair, Karina S.; Leibenluft, Ellen; Blair, R. James R. (Frontiers in Psychiatry, 2021)
Background: Irritability and callous-unemotional (CU; reduced guilt/empathy) traits vary dimensionsally in the typically developing population but may be particularly marked in youth with conduct disorder (CD). While these dimensional traits are positively correlated, they have been associated with divergent forms of dysfunction, particularly with respect to threat processing (i.e., irritability with increased, and CU traits with decreased, threat responsiveness). This suggests that interactions between these two dimensions may be complex at the neurobiological level. However, this issue has received minimal empirical attention. Methods: The study included 105 adolescents (typically developing and cases with CD; N = 59). They were scanned with fMRI during a looming threat task that involved images of threatening and neutral human faces or animals that appeared to be either looming or receding. Results: Significiant irritability-by-CU traits-by-Direction-by-Emotion interactions were seen within right thalamus/PAG, left lingual gyrus and right fusiform gyrus; irritability was positively associated with the BOLD response for Looming Threatening versus Receding Threatening trials, particularly for youth with low CU traits. In contrast, CU traits were negatively associated with the same differential BOLD response but particularly for youth showing higher levels of irritability. Similar findings were seen within left ventral anterior and posterior cingulate cortices, though the addition of the interaction with CU traits was only seen at slightly more lenient thresholds. Conclusions: The results support previous work linking irritability to increased, and CU traits to reduced, threat responsiveness. However, for adolescents with high irritability, if CU traits are also high, the underlying neuropathology appears to relate to reduced, rather than increased, threat responsiveness.